2019
DOI: 10.3847/2041-8213/ab564d
|View full text |Cite
|
Sign up to set email alerts
|

First Results from TESS Observations of Comet 46P/Wirtanen

Abstract: We report on initial results from 20 days' worth of TESS spacecraft observations of comet 46P/Wirtanen. The long-duration, high-cadence measurements show a 2018 September 26 outburst that exhibited a two-phase, 0.5 mag brightening profile, and may be the best temporally characterized natural outburst ever recorded. Gas velocities from the outburst peaked at 800 m s −1 , while dust expanded at only 10s of m s −1 . Coadded images also revealed a previously unreported dust trail that extends beyond the 24 • field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Our general assumption is that all outbursts are brief events, lasting 1 day, and that the ejecta can continue to be observed well after the outburst is over. This assumption is consistent with the analysis of 30-min cadence observations of outburst B with the Transiting Exoplanet Survey Spacecraft (TESS ) by Farnham et al (2019), who found coma brightening ceased after 8 hr. Short outburst timescales, 1 hr, are also consistent with the high spatial resolution observations of outbursts at 9P/Tempel 1 by Deep Impact (Farnham et al 2007) and at 67P/Churyumov-Gerasimenko by Rosetta (Knollenberg et al 2016;Vincent et al 2016;Agarwal et al 2017;Bockelée-Morvan et al 2017;Rinaldi et al 2018).…”
Section: Search For Fragmentssupporting
confidence: 90%
See 4 more Smart Citations
“…Our general assumption is that all outbursts are brief events, lasting 1 day, and that the ejecta can continue to be observed well after the outburst is over. This assumption is consistent with the analysis of 30-min cadence observations of outburst B with the Transiting Exoplanet Survey Spacecraft (TESS ) by Farnham et al (2019), who found coma brightening ceased after 8 hr. Short outburst timescales, 1 hr, are also consistent with the high spatial resolution observations of outbursts at 9P/Tempel 1 by Deep Impact (Farnham et al 2007) and at 67P/Churyumov-Gerasimenko by Rosetta (Knollenberg et al 2016;Vincent et al 2016;Agarwal et al 2017;Bockelée-Morvan et al 2017;Rinaldi et al 2018).…”
Section: Search For Fragmentssupporting
confidence: 90%
“…Our first outburst image appears to taken ∼12 hr before the outburst peak as observed by Farnham et al (2019). Therefore, our peak brightness estimate may be low by 0.1 mag.…”
Section: Outburstsmentioning
confidence: 65%
See 3 more Smart Citations